Optimization of β-cyclodextrin-based extraction of antioxidant and anti-browning activities from thyme leaves by response surface methodology - Favre, Leonardo Cristian (2018)
Thyme (Thymus vulgaris) has been demonstrated to extend the shelf-life of food products, being also a potential source of bioactive compounds. The aim of this research was to optimize the ultrasound assisted extraction employing β-cyclodextrin aqueous solutions as no-contaminant technology and Response Surface Methodology to obtain thyme extracts with the maximum antioxidant capacity. The optimal extraction conditions were: a solution of β-ciclodextrin 15 mM, an ultrasonic treatment time of 5.9 min at a temperature of 36.6 °C. They resulted in an extract with a polyphenolic content of 189.3 mg GAE/mL, an antioxidant activity (DPPH[rad]) of 14.8 mg GAE/mL, and ferric reducing/antioxidant power (FRAP) of 3.3 mg GAE/mL. Interestingly, the extract demonstrated to inhibit the production of Maillard browning products and can be considered a potential antiglycant agent. The obtained data is important for developing eco-friendly technologies in order to obtain natural antioxidant extracts with a potential inhibitory capacity of Maillard glycation reaction.